2006
DOI: 10.1889/1.2210802
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric nanoparticle/liquid-crystal colloids for display applications

Abstract: A non-synthetic approach to modify liquid crystals (LCs) by dispersing low concentrations of ferroelectric nanoparticles is reported. These dilute colloids are stable and appear similar to a pure LC. However, by changing the concentration and the type of ferroelectric particles, the physical properties of the LC materials can be tailored, including the nematic isotropic transition temperature (T NI ), the dielectric constants, the birefringence (∆n), elastic constants, and the threshold voltage. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 10 publications
1
38
2
Order By: Relevance
“…5,6 Another example of hybrid materials are the suspensions of ferroelectric nanoparticles 7 in nematic liquid crystals. Liquid crystals functionalized in this way show increased phase transition temperatures as well as dielectric and optical anisotropy 8 and have potential applications in, for example, displays 9 as well as for photorefractive systems. 10 In this study, we explored the impact of nanoparticles on liquid crystals most suitable for optoelectronic applications, namely, low refractive index liquid crystals.…”
Section: Ferroelectric Nanoparticles In Low Refractive Index Liquid Cmentioning
confidence: 99%
“…5,6 Another example of hybrid materials are the suspensions of ferroelectric nanoparticles 7 in nematic liquid crystals. Liquid crystals functionalized in this way show increased phase transition temperatures as well as dielectric and optical anisotropy 8 and have potential applications in, for example, displays 9 as well as for photorefractive systems. 10 In this study, we explored the impact of nanoparticles on liquid crystals most suitable for optoelectronic applications, namely, low refractive index liquid crystals.…”
Section: Ferroelectric Nanoparticles In Low Refractive Index Liquid Cmentioning
confidence: 99%
“…As the previous studies suggested [5,7], the change in the properties of the nanoparticles suspensions could be related to the ferroelectric nps affecting the order parameter of host LC material. Therefore, we decided to prepare ferroelectric suspensions with LC materials with simpler structure, but composed of compounds similar to LC 2020.…”
Section: [Insert Figure 2 About Here]mentioning
confidence: 83%
“…In [4,5] there is a detailed description of the preparation the nematic ferroelectric nps solutions. We used the suspensions nps1, nps2 and nps3 with two materials 6CHBT and 2020.…”
Section: About Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, also non-elongated particles of dielectric, paramagnetic, super-paramagnetic, ferroelectric or ferromagnetic nature can be employed and dispersed isotropically within different liquid crystal phases [1,22,23]. These particles cannot exhibit a preferred directionality, but they can interact to form anisotropic clusters, exhibit chaining mediated via the interaction of defects formed in the vicinity of the inclusion [3], or form patterns under the application of external fields, like it was studied in this investigation.…”
Section: Introductionmentioning
confidence: 99%